Novel composite structures based on cobalt phthalocyanine/graphene oxide: Identification of potential drug candidates to treat Alzheimer's disease and diabetes - Gunsel, Armagan; Gunsel, Hilal; Taslimi, Parham; Taskin-Tok, Tugba; Erden, Busra Aksoy; Bilgicli, Ahmet T.; Sadeghian, Nastaran; Taslimi, Parham; Sadeghian, Nastaran; Erden, Büşra Aksoy (Elsevier Science Sa, 2024)
This study produced novel cobalt phthalocyanine (CoPc) (2) and its graphene oxide (GO) composites (2a-2f) and examined their impact on several metabolic enzymes, including alpha-glycosidase (alpha-Gly), achetylcholinesterase (AChE) and butyrylcholinesterase (BChE). IC50 values showed that when compared to conventional inhibitors, all the compounds demonstrated strong inhibitory effects against all targets. The ranges for the Ki values of the compounds containing the AChE, BChE, and alpha-glycosidase enzymes were 26.15 f 3.85-48.26 f 7.43, 5.46 f 0.57-10.68 f 0.78, and 2.20 f 0.11-22.41 f 2.60 nM, in that order. In addition, pharmacodynamic studies, the model form of new CoPc/GO composites, their structural orientations in the active sites of AChE, BChE and alpha-Gly enzymes, respectively, their binding interaction mechanism, and even their drug potential were investigated. The relevant compound (CoPc/GO) shows a binding energy trend of-12.40,-12.30 and-12.10 kcal/mol to alpha-Gly, AChE and BChE enzymes, respectively. In addition, it was determined that the compounds exhibited cytotoxic effects against human breast cancer cells. After more than 20 years of usage, cholinesterase inhibitors (ChEIs) are still a crucial component of the therapy of Alzheimer's disease (AD). In multiple multicenter, well-controlled trials, only ChEIs have consistently demonstrated efficacy against AD; as a result, they have been widely approved by national regulatory authorities. Even if there have been a lot of ChEI discoveries recently, drug discovery is a continuous process that involves looking for novel strategies and chemotypes.
Keywords: Cobalt Phthalocyanine; Graphene Oxide; Enzyme Inhibition; Anticancer; Molecular Docking